Ultrasonic-assisted extraction of cellulose from sugarcane bagasse - Phuang, Ke Shong (2019)
The large amount of lignocellulosic biomass have contributed to the environmental issues. Therefore, it is essential to recycle them and convert it into more useful products via environmental friendly technology. In this research, sugarcane bagasse (SCB) is used as the feedstock for cellulose extraction since it can be easily found worldwide with about 50 %(w/w) of cellulose content. In addition, ultrasonic-assisted alkaline extraction was used as the green technology to obtain the cellulose with vital consideration to reduce the chemical and energy usage compared to current conventional extraction technology. The SCB was autoclaved with distilled water before undergo ultrasonic extraction in alkali medium. The treatments were carried out by manipulating three different processing parameters, which are ultrasonic amplitude of 20 %, 30 % and 40 %, temperature at 70 oC, 80 oC and 90 oC and concentration of potassium hydroxide solution vary from 0.25 M to 1.25 M, with interval of 0.25 M. Approximate 56.58 %(w/w) to 83.22 %(w/w) of cellulose has been successfully extracted from SCB samples. It was found that SCB treated at ultrasonic amplitude of 30 %, 80 oC and 1.25 M KOH resulted the highest amount of cellulose. This treated SCB sample was then further converted into carboxymethyl cellulose (CMC) through alkalization with 17.5 %(w/v) NaOH and etherification process by addition of sodium monochloroacetate (SMCA). The synthesis process gave CMC with degree of substitution of 0.3624. A low DS was obtained as the experiment is not carried out in optimum condition. Meanwhile, a film is successfully produced, further assure the properties of produced CMC. The characteristics of each of the treated SCB and CMC were analysed by Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC) and High Pressure Liquid Chromatography (HPLC). The testing further verified that the properties of cellulose and CMC extracted from SCB are significantly promising for large scale production.